Neural processing associated with cognitive empathy in pedophilia and child sexual offending. Issue 8 (15th December 2021) - Schuler, Miriam; Mohnke, Sebastian; Amelung, Till; Beier, Klaus M; Walter, Martin; Ponseti, Jorge; Schiffer, Boris; Kruger, Tillmann H C; Walter, Henrik
Abstract: Behavioral studies found evidence for superior cognitive empathy (CE) in pedophilic men without a history of child sexual offending (P − CSO) compared to pedophilic men with a history of child sexual offending (P + CSO). Functional magnetic resonance imaging (fMRI) studies also point to differences between P − CSO and P + CSO. Neural processing associated with CE has not yet been investigated. Therefore, the present study aimed to explore the neural correlates of CE in subjects with pedophilia with (P + CSO) and without (P − CSO) child sexual offending. 15 P + CSO, 15 P − CSO and 24 teleiophilic male controls (TC) performed a CE task during fMRI. We observed reduced activation in the left precuneus (Pcu) and increased activation in the left anterior cingulate cortex (ACC) in P − CSO compared to P + CSO. P − CSO also showed stronger connectivity between these regions, which might reflect a top-down modulation of the Pcu by the ACC toward an increased self-focused emotional reaction in social situations. There was also evidence for increased right superior temporal gyrus activation in P − CSO that might constitute a potentially compensatory recruitment due to the dampened Pcu activation. These findings provide first evidence for altered neural processing of CE in P − CSO and underline the importance of addressing CE in pedophilia and CSO in order to uncover processes relevant to effective prevention of child sexual abuse.